The potential for reduced consumption of high- emission energy in Kenya’s dairy sector - Wilkes, Andreas; Dijk, Suzanne van; Odhong’, Charles (2018)
Kenya’s dairy processers are increasingly paying attention to energy efficiency in their operations. This is driven by a squeeze on profit margins due to falling international milk prices and high domestic production costs, and energy efficiency requirements of newly enforced regulations on large energy consuming facilities. In processing plants, there is significant potential to reduce consumption of electricity, as well as diesel and oil used in steam generation. Reduced use of water and cleaning chemicals, and lower milk losses, can further contribute to cost savings. Cost-effective options for reducing energy use in Kenya’s 597 cooling centres and satellite coolers requires further investigation. Because energy efficiency is a releatively new field, dairy processing companies and banks are wary of investing. Provision of technical assistance to both processors and banks and concessional credit lines could help both dairy processors and banks to invest in the significant energy conservation opportunities available.